Comparison of the biomechanical stability of transverse and oblique screw trajectories in retrograde intramedullary nailing of supracondylar femur fractures. (December 2022) - Muriuki, Muturi G.; Sonn, Kevin A.; Brinkmann, Elyse J.; Blank, Kenneth R.; Havey, Robert M.; Patwardhan, Avinash G.; Bernstein, Mitchell
Abstract: Background: The goal was to determine the effect of addition of oblique trajectory distal interlock screws to a retrograde intramedullary femoral nail on implant stability (stiffness), cycles to failure and mode of failure. The hypothesis was that addition of oblique screws would increase implant stability and number of loading cycles to failure. Methods: Eight matched pairs were tested; one femur implanted with a femoral nail with only transverse distal interlock screws and the other with transverse and oblique interlock screws. Axial compressive load was applied to the femoral head and the gluteal tendon was tensioned vertically to simulate standing or at 45° to the sagittal plane to simulate stair climbing. Loads were cycled to increasing amplitude until failure of fixation (10 mm displacement or 10° rotation). Findings: In simulated standing, oblique screw specimen had greater sagittal bending (bowing) than transverse only specimen. Transverse (axial) plane motion was higher in simulated stair climbing in oblique screw specimen. Oblique screw specimen had higher sagittal plane translation at 600 N of load. At 300 N, oblique screw specimen had lower internal-external rotation than transverse only specimen. A larger number of cycles to failure were observed in four oblique screw of seven paired specimen. Failure (10 mm or 10 degrees of motion) was only achieved during simulated stair climbing. Interpretation: Our hypothesis that adding oblique screws improves fixation was rejected. Activities of daily living other than standing may constitute a challenge to fracture fixation; fixation failure occurred at lower loads in simulated stair climbing than standing. Highlights: Simulated stair climbing was more challenging than standing to fracture fixation. In 15/16, 10° of motion occurred at the fracture site before 10 mm of motion. Additional intramedullary nail locking screws did not improve fracture fixation.